Pengaruh Endorser Periklanan Terhadap Keputusan Pembelian (Studi Kasus Pelembab Wajah Ponds Flawless White Pada Mahasiswa STIT dan STEBIS Kota Pagar Alam) - Dismita Citra Dewi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2019)
This study aims to determine the effect of advertising endorsers on the purchase decision of Ponds Flawless White facial moisturizers, and determine which of the variables between attractiveness, trustworthiness, and expertise is the most dominant influence on purchasing decisions. Respondents involved in this study were 100 people, the method used was non-probability sampling, namely purposive sampling. The method of data analysis is done by multiple linear regression using SPSS software. The results of this study indicate that overall advertising endorsers have an influence on purchasing decisions. Of the three advertising endorser variables studied, namely attractiveness, trustworthiness and expertise, only the variable expertise has a statistically influential effect on purchasing decisions of 0.293. In this study a new regression model was obtained, namely Y = 5.229 + 0.293 X3. So that companies can maintain efficiency in advertising, you should choose an endorser who really has high credibility. And also companies need to pay attention to product quality to face increasing competition